Wild West, Wild East. Western and the Polish question - Jerzy Franczak (Przestrzenie Teorii)
The article reconstructs poetics and politics of Polish westerns, focussing on the two most re-nowned examples of the genre: The Law and the Fist (1964) or The Wolves' Echoes (1968). They are set in the western or eastern   borderlands of post-war Poland (1945–1948) and depict the struggles of righteous militiamen against plunderers and looters. The analysis is based on classical theories formulated by A. Bazin, J. Kitses and W. Wright and aims to highlight hidden contradic-tions between the rules of film genre, the requirements of veracity, and propagandist manipula-tion. These movies reinforce the official politics of memory of the Polish People’s Republic. The Law and the Fist contribute to the discourse on the ‘Recovered Territories’ and renew the Piast concept of returning these territories to the traditional Polish homeland. In turn, The Wolves' Echoes shapes the collective memory of the Bieszczady Mountains and justifies ethnic homogene-ity of this borderland.